Plate Tectonic Setting of Newfoundland Mineral Deposits - Strong, D. (Geoscience Canada, 1974)
Summary Newfoundland Paleozoic mineral deposits show many characteristics which allow for their classification in terms of distinct plate tectonic environments. The Lower Paleozoic deposits are mainly stratigraphically controlled, ranging from Mississippi Valley type zinc deposits, ophiolite, Cu, Cr and asbestos, Kuroko-type polymetallic Zn, Cu, Pb, Ag, Au, to shallow water manganese and oolitic hematite deposits. The upper Paleozoic deposits are mainly associated with Devonian granitoid intrusions (e.g., Cu-Mo and/or F deposits), with minor sedimentary Zn-Pb and Ba-Sr in intra-continental Carboniferous sediments. Other less important deposits likewise fit plate tectonic models.